On Markov measure-valued processes in a finite space - Ostapenko, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider stochastic flows with interaction in a finite phase space. The flows with variable generators generating evolutionary measure-valued processes are described. The influence of the interaction of particles on the entropy of the flow is analyzed.